Analysis of the Need for Developing an Ethnoscience-Based Module on Plant Material Biology (Plantae) to Improving Learning Outcomes - Anattri, Lega; Yelianti, Upik; Subagyo, Agus; Falani, Ilham (Jurnal Pijar Mipa, 2024)
The development of ethnoscience-based modules in biology learning, especially on plant material (Plantae), is an essential aspect of efforts to improve learning outcomes. By combining ethnographic and scientific approaches, this module is expected to consider students' cultural context better so as to increase their engagement and understanding of the material. This research aims to analyze the need to develop ethnoscience-based modules, and the importance of analyzing module needs today as an effort to improve biology learning outcomes on plant material (Plantae). This research uses qualitative research with a descriptive approach. The research method used is development research with stages that include identifying needs, planning, development, testing, and evaluation. The sampling technique was carried out using purposive sampling, with a sample of 60 students, and only 10 students, as well as 3 biology subject teachers at SMAN 1 Sungai Penuh, were selected for interviews. Data was collected through observation, field studies, documentation, and interviews and analyzed descriptively. The needs identification results show that there is a high need for the development of ethnoscience-based modules to strengthen students' understanding of plant material. The module is designed by considering the local cultural context and traditional knowledge, which can increase students' absorption of learning material. Module trials were carried out involving students as research subjects, and the results showed a significant increase in understanding of plant material. In addition, the positive response from students and teachers to the module confirms its effectiveness in improving biology learning outcomes. The newest thing in this research is a module developed with elements of ethnoscience by combining scientific concepts with scientific concepts that exist in society so that they can be expressed in a module. So, it can be concluded that the analysis of module needs is indeed critical and necessary in biology learning, especially plant material, which teachers and students can use.